Analisis Nilai Tambah Biji Kakao Menjadi Produk Coklat Olahan - Jumrah, Jumrah; Iswandi, R Marsuki; Yunus, Lukman (Department of Agribusiness Halu Oleo University Kendari Southeast Sulawesi, 2018)
This study aims to determine the processing of cocoa beans into cocoa products processed, to determine the added value of cocoa beans into cocoa products processed, and to identify the obstacles encountered in increasing the added value of cocoa beans into chocolate products processed in the laboratory FTIP UHO Kendari. Determination of purposive sample is done with the consideration that the Laboratory of Food Technology FTIP UHO is the only college in Southeast SulawesiÂ perform processing cocoa beans into chocolate products processed. The data was processed using descriptive qualitative analysis and the analysis of value-added. The results showed that (1) The processing of cocoa beans into chocolate products processed in the laboratory FTIP UHO Kendari include: preparation of cocoa beans, sorting, roasting, cooling, separation of seeds, roasting nib, cooling nib, milling pasta rough, grinding fine paste, storage pasta, dough-making, printing and freezing. (2) Value-added processing of cocoa beans into chocolate products in the Laboratory FTIP UHO for every kilogram of raw material cocoa is Rp 312.252,26/kg with added value ratio of 41,65% which is an increase each output value by Rp. 1 will increase the added value amounting to Rp. 41,65. Labor's share amounted to 30,01% and the share of profits amounted to 29,15%, (3) The constraints that exist in increasing the added value of cocoa beans into chocolate products Processed marketing network cocoa preparations have not been too broad, consumers of these products amounted to 83% of lecturers / employees in the scope of FTIP UHO, indoor processing cocoa beans into chocolate products processed still as well as the limited durability of processed cocoa products is very low at only can last for 8 hours so easy to melt